Neurokinin-1 inhibitors in the prevention of nausea and vomiting from highly emetogenic chemotherapy: a network meta-analysis - Omar Abdel-Rahman (Therapeutic Advances in Medical Oncology, 2016)
A network meta-analysis of the comparative effectiveness of neurokinin 1 (NK-1) inhibitors in the prophylaxis of highly emetogenic chemotherapy induced nausea and vomiting has been conducted. Eligible studies included randomized trials evaluating aprepitant, fosaprepitant, netupitant (NEPA), casopitant and rolapitant containing regimens in the setting of highly emetogenic chemotherapy. Primary outcomes of interest include complete response (CR) and rate of no significant nausea. After preclusion of ineligible studies, 19 studies were included in the final analysis. The majority of the regimens containing NK-1 inhibitors (including NEPA, aprepitant/palonosetron (palono)/dexamethasone (dexa), casopitant/granisetron (grani) or ondansetron (ondan)/dexa, aprepitant/ondan/dexa) are better than regimens not containing them (palono/dexa, ondan/dexa, grani/dexa) in terms of achieving a CR in the overall phase. Moreover, casopitant/grani or ondan/dexa and aprepitant/grani or ondan/dexa are better than rolapitant/ondan or grani/dexa in terms of CR achievement [odds ratio (OR) 1.62, 95% credible interval (CrI) 1.14–2.23, and OR 1.28, 95% CrI 1.01–1.59, respectively]. Taking into consideration the limitations of cross-trial comparisons, regimens containing neurokinin inhibitors are associated with higher CR rates than regimens not containing them. Moreover, casopitant and aprepitant regimens seem to be more effective than rolapitant regimens.